2009
DOI: 10.1007/s00105-009-1744-y
|View full text |Cite
|
Sign up to set email alerts
|

Suizidgedanken, Angst und Depression bei erwachsenen Neurodermitikern

Abstract: Suicidal ideation, anxiety and depression are important factors, which should be addressed when treating atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 25 publications
3
12
0
2
Order By: Relevance
“…Using a population-based sample from the U.S., Yang and colleagues found an increased likelihood of a depressive disorder in adults with AD (OR>2.0.) and a controlled study from Germany found increased rates of anxiety, depression, and suicidal ideation in adults with AD that correlated with disease severity [110-111]. Our group recently confirmed the association between AD and other mental health disorders including anxiety, depression, conduct disorder, and autism in a large U.S. pediatric population [103].…”
Section: Mental Healthsupporting
confidence: 55%
“…Using a population-based sample from the U.S., Yang and colleagues found an increased likelihood of a depressive disorder in adults with AD (OR>2.0.) and a controlled study from Germany found increased rates of anxiety, depression, and suicidal ideation in adults with AD that correlated with disease severity [110-111]. Our group recently confirmed the association between AD and other mental health disorders including anxiety, depression, conduct disorder, and autism in a large U.S. pediatric population [103].…”
Section: Mental Healthsupporting
confidence: 55%
“…26 A controlled study from Germany found increased rates of anxiety, depression, and suicidal ideation in adults with AD. 27 Three recent studies found an increased risk of autism in children with atopic diseases. 19,20,28 These studies of autism and AD were limited by the lumping of all atopic disease into one category, however.…”
Section: Discussionmentioning
confidence: 99%
“…These effects might be reflected by a marked increase in suicidal ideation in patients with AD. [6][7][8] Despite the increasing worldwide incidence of AD, treatments are limited, with only 3 approved (depending on country) systemic therapeutic options for patients with severe disease who are inadequate responders to topical agents: oral corticosteroids, oral cyclosporin A (CsA), and UVA1/narrow-band UVB (NB-UVB) phototherapy. 9 These therapies are not uniformly effective, and their use is limited by toxicity (corticosteroids and CsA) or inconvenience (NB-UVB).…”
mentioning
confidence: 99%